Red Sea: Connecter and divider. Disruption waves from the Arabian Gulf to the Horn of Africa - Annette Weber (Stiftung Wissenschaft und Politik (SWP), 2017)
The Red Sea is a vital pathway for goods, people, arms, and livestock. European trade with Asia passes through here as well as oil from the Gulf to the Mediterranean, and a sizeable amount of global marine cargo is hauled through the Suez Canal and the Red Sea into the Indian Ocean. In addition to its significance as a trade route, the Red Sea is a lane for migration between the Gulf and the Horn of Africa and a bridge for roving terrorists. Its water connects the Horn of Africa with the Gulf countries, although it also separates African and Arab political and social cultures. Moreover, many issues are contested in the Red Sea region, ranging from military control to political Islam. In order to avoid further rifts between the Horn of Africa countries as a consequence of the disruptive politics of the Gulf, the Horn needs to perceive itself as a region and find common interests rather than becoming fragmented and weakened. The stability of the Horn of Africa as well as the security of its trade routes are of vital interest to European countries and economies.
Keywords: 320